Efficient Addition of Waste Glass in MK-Based Geopolymers: Microstructure, Antibacterial and Cytotoxicity Investigation - Dal Poggetto, Giovanni (Polymers (Basel), 2021)
Reuse of waste glass can significantly decrease the quantity of waste to be treated or disposed of in landfills, allowing to both diminish the ecological damage and to reduce the costs of transportation for removal. Geopolymer mixes with diverse percentages (20, 50 and 60 wt%) and with different grain size ranges (37 μm < diam < 53 μm; 75 μm < diam < 105 μm) of waste glass and the residual part of pure metakaolin were prepared by addition of NaOH and sodium silicate as alkaline activator solutions. The effect of waste glass on the mechanical and microstructure of new geopolymers has been explored in this study. Fourier transform infrared spectroscopy (FTIR) evidenced the reactivity of waste glass in terms of Si–O and Si–O–Al bonds, more evident for the finer waste glass powder. The consolidation of the materials has been established by reduced weight loss in water and decreased pH and ionic conductivity of the eluate after 7, 14 and 28 days of curing at room temperature. The decrease of the mechanical properties with waste glass content was less evident for the finer glassy powders, yet the value of about 4-5 MPa indicates their potential use as non-structural materials. The consolidated final materials were tested for their effects on the microbial growth of Escherichia coli and Enterococcus faecalis after 24 and 48 h, respectively. The samples showed a very limited and absent inhibition zone, for fine and coarse grain size ranges, respectively. Finally, the cytotoxicity tests accomplished the ecological valuation of the final consolidated products.